2018
DOI: 10.2196/mhealth.9729
|View full text |Cite
|
Sign up to set email alerts
|

Digital Food Records in Community-Based Interventions: Mixed-Methods Pilot Study

Abstract: BackgroundA pressing need exists to understand and optimize the use of dietary assessment tools that can be used in community-based participatory research (CBPR) interventions. A digital food record, which uses a mobile device to capture the dietary intake through text and photography inputs, is a particularly promising mobile assessment method. However, little is understood about the acceptability and feasibility of digital food records in CBPR and how to best tailor dietary assessment tools to the needs of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Thirdly, the consecutive 3-day dietary record instead of generally applied non-consecutive ones was used for the assessment of dietary intake. However, the consecutive 3-day method was described in the methodological guide on nutrition research [ 34 ] and is still used in nutritional analyses by other authors [ 56 , 57 , 58 ]. For confirmation of the results obtained, however, using the non-consecutive method on a larger study group of children is advisable, particularly for the micronutrient evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the consecutive 3-day dietary record instead of generally applied non-consecutive ones was used for the assessment of dietary intake. However, the consecutive 3-day method was described in the methodological guide on nutrition research [ 34 ] and is still used in nutritional analyses by other authors [ 56 , 57 , 58 ]. For confirmation of the results obtained, however, using the non-consecutive method on a larger study group of children is advisable, particularly for the micronutrient evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Poelman et al provide an example of a digital food tracking system that could be embedded into social media apps to understand how food choices are influenced by the real-world food environment [33]. Another option is the use of digital food record mobile apps, such as FitNinja (Vibrent Health), with image recognition software to collect nutrient content; these have been found to be acceptable tools for digital food records of real-world food intake [34]. Additionally, shared food posts, such as fruits and vegetables marked by peer likes among user networks in social media environments, may represent reinforcement of positive-or any valence-nutrition behaviors as positive, well-liked behaviors [35].…”
Section: Principal Findingsmentioning
confidence: 99%
“…A 2014 review of dietary assessment found that user satisfaction was high for six studies using mobile phones for dietary assessment, with one study reporting a low user satisfaction [10]. Two newer studies also corroborate with the general acceptance of mobile food records among adults, including in a community setting [18,19].…”
Section: Discussionmentioning
confidence: 85%